France : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
The buoyant economic record is attributable to a favorable external environment; supportive monetary conditions; protracted wage moderation; gradual labor market reforms; and sizable cuts in tax rates and social security contributions. The government reasserted its intention to achieve fiscal balance and substantially lower the public debt-to-gross domestic product ratio over the long term. To reach these goals, there is a need to tackle civil service, health care, and pension reform and to strengthen the framework for fiscal policy and focus it more on binding medium-term expenditure norms.